RELATIONSHIP BETWEEN MOISTURE CONTENT AND FLAMMABILITY OF CERRADO SPECIES IN SOUTHERN TOCANTINS - de Oliveira, Marcileia Dias; Giongo, Marcos (Floresta, 2022)
This study aimed to analyze the relationship between moisture content and flammability of nine plant species from the Cerrado in southern Tocantins. The species studied were: Machaerium brasiliense, Qualea grandiflora, Luehea grandiflora, Campomanesia guaviroba, Astronium fraxinifolium, Curatella americana, Bauhinia forficata, Vatairea macrocarpa, and Anacardium Occidentale. The plants were analyzed at four moisture contents (M1, M2, M3, and M4). For each level, 50 samples (1 g ± 0.1 g) of each species were collected, and 50 repetitions of burning were performed. The parameters analyzed were: time to ignition (TI), frequency of ignition (FI), duration of combustion (DC), combustion index (CI), flammability value (FV), and height of flames (HF). Our results showed that moisture contents influence flammability in Cerrado plant species. The correlation coefficients between moisture and flammability parameters were r = 0.951 (TI), r = -0.962 (DC), r = -0.977 (HF), and r = -0.988 (FI).